An Analysis Of Factors Influencing Bpjs Patient Loyalty Based On Customer Satisfaction Theory At Bandung General Hospital Medan - Windri Mutiara Matondang; Chrismis Novalinda Ginting; Ali Napiah Nasution (Jurnal Ners, 2025)
This study aims to analyze the effect of marketing strategies and medical device product facilities on increasing the number of patients at Dr. Pirngadi Regional General Hospital, Medan. Competition in the healthcare industry requires hospitals to not only provide quality medical services but also implement effective marketing strategies and provide adequate healthcare facilities to attract and retain patients. This study used a quantitative approach with a descriptive correlational design. The study population included all patients visiting Dr. Pirngadi Regional General Hospital during the last three months, with a total sample of 78 respondents selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that marketing strategies and medical device facilities had a positive effect on increasing the number of patients, with medical device facilities having a more dominant influence. This finding emphasizes the importance of synergy between appropriate marketing strategies and improved medical facilities in building patient trust, strengthening loyalty, and increasing hospital competitiveness sustainably amidst increasingly fierce healthcare competition.